Nafsu Manusia Dalam Karya Film Tari Human Passions - Arifianto, Budi Dwi (Capture : Jurnal Seni Media Rekam, 2014)
Filmas an audio visual art has evolved into an important part of human civilization,especially in popular culture. One of genre simplying freedom of expression inaccordance with the purpose and desired by the creator of ideas is experimental film.On the one hand, the dancewas chosenas theembodiment ofthe expression ofthe bodywill beconveyed in thevoice of humanity aesthetic rules. Human Passions is a collaboratework ofa udio visual art and the art of dance. The initial idea is knitted from humanexperience as acreator who is accompanied by variouspassions. This film consist oftwo act, â€œThe Birth of Passionsâ€andâ€Live With Passionâ€.The body becomes the centralobject of the creation of this work. Choreography that plotshuman life is framed in acinematic composition. Human and the spirit are symbolized by oil lamp. Oil is thehumanâ€™s soul as light forces for lightening the spirit of human passions. This dance filmis a personal statement from the creator about human passions. The audiences as humansare exaggerated to let them know about their spirit of passions.Keywords: dance,film, human passions